A Mathematical Model of a Horizontal Direct-Fired Strip Annealing Furnace. Issue 20 (2016) - Maislinger, F.; Niederer, M.; Steinboeck, A.; Strommer, S.; Kugi, A.
Abstract: A tractable mathematical model of a horizontal direct-fired furnace is presented. The first-principles model captures the essential non-linearities of the furnace and includes submodels for the flue gas, the rolls, the wall, and the strip. These submodels are interconnected by the heat transfer mechanisms conduction, convection, and radiation. For both the identification of unknown parameters and the validation of the developed model, measurement data from the considered furnace is used. The model is computationally inexpensive and thus suitable for model-based control and real-time optimization.